3m-2(m+7)=m-14

Simple and best practice solution for 3m-2(m+7)=m-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3m-2(m+7)=m-14 equation:


Simplifying
3m + -2(m + 7) = m + -14

Reorder the terms:
3m + -2(7 + m) = m + -14
3m + (7 * -2 + m * -2) = m + -14
3m + (-14 + -2m) = m + -14

Reorder the terms:
-14 + 3m + -2m = m + -14

Combine like terms: 3m + -2m = 1m
-14 + 1m = m + -14

Reorder the terms:
-14 + 1m = -14 + m

Add '14' to each side of the equation.
-14 + 14 + 1m = -14 + 14 + m

Combine like terms: -14 + 14 = 0
0 + 1m = -14 + 14 + m
1m = -14 + 14 + m

Combine like terms: -14 + 14 = 0
1m = 0 + m
1m = m

Solving
1m = m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-1m' to each side of the equation.
1m + -1m = m + -1m

Combine like terms: 1m + -1m = 0
0 = m + -1m

Combine like terms: m + -1m = 0
0 = 0

Simplifying
0 = 0

The solution to this equation could not be determined.

See similar equations:

| log(2x)+log(x)=11 | | n-3/4 | | (48w^9x^3/3w^5x^5)^1/2 | | -7(t+5)=14 | | 4/5x=2 | | -4x=-18+5x | | (5x^0/10x^-3y^2)^2 | | 12/x=5/9 | | 13w-9w+w=20 | | 5x+4(3-2x)=6 | | 20s-20s+s+s+4s=12 | | 5/9-12/x | | 6a+a=-7 | | 2(2x+3)-7x=18+5(x+3x) | | 14v+4v-18v+v=7 | | 4[5(1)-3]= | | ln*4x^2=21 | | S/Q-T/Q=1 | | 11k+-6k-k=-2 | | x-45/2=25 | | x+y+9z=10 | | 8z-6z=20 | | (x^4)*e(x)-7=0 | | 2d-2d+3d=3 | | (7y+6)-(3+6y)=8 | | 4x(-114+x^2)=0 | | 26x^2+3x-8=0 | | 8(y-3)+2y=18 | | 10=10-2x | | 2d-d+1=13 | | C=3.14/2 | | 0=-16t+46t+6 |

Equations solver categories